Studi Literatur: Evaluasi Ragam Model Pembelajaran dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar pada Mata Pelajaran Matematika - Utami, Adiratna Dwi; Widyani, Agustina Tri; Ristiningsih, Dika; Wijayanti, Murwani Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The advancement of 21st century education demands mastery of higher-order thinking skills, especially critical thinking, but learning in elementary schools is still dominated by conventional approaches that are teacher-centered and lack active student involvement, making it less effective in developing these abilities. This study aims to evaluate learning models that effectively improve critical thinking skills among elementary school students. Using the narrative review method, this study analyzed the literature on the implementation of innovative learning approaches. The results showed that learning models such as Problem-Based Learning (PBL), Discovery Learning, and Project-Based Learning (PjBL), as well as cooperative strategies such as Jigsaw, Think Pair Share (TPS), Two Stay Two Stray (TSTS), Teams Games Tournament (TGT), and Make a Match proved to be effective in learning. These models can increase students' participation, collaboration, and logical and analytical thinking skills. Therefore, the application of diverse and innovative learning models is a strategic approach to strengthen critical thinking in elementary school mathematics education.Kemajuan pendidikan abad ke-21 menuntut penguasaan keterampilan berpikir tingkat tinggi, khususnya berpikir kritis, namun pembelajaran di sekolah dasar masih didominasi pendekatan konvensional yang berpusat pada guru dan minim keterlibatan aktif siswa, sehingga kurang efektif dalam mengembangkan kemampuan tersebut. Penelitian ini bertujuan untuk mengevaluasi model pembelajaran yang secara efektif meningkatkan kemampuan berpikir kritis di kalangan siswa sekolah dasar. Dengan menggunakan metode tinjauan naratif, penelitian ini menganalisis literatur tentang penerapan pendekatan pembelajaran yang inovatif. Hasil penelitian menunjukkan bahwa model pembelajaran seperti Problem-Based Learning (PBL), Discovery Learning, dan Project-Based Learning (PjBL), serta strategi kooperatif seperti Jigsaw, Think Pair Share (TPS), Two Stay Two Stray (TSTS), Teams Games Tournament (TGT), dan Make a Match terbukti efektif digunakan dalam pembelajaran. Model-model tersebut dapat meningkatkan partisipasi, kolaborasi, serta kemampuan berpikir logis dan analitis siswa. Oleh karena itu, penerapan model pembelajaran yang beragam dan inovatif merupakan pendekatan strategis untuk memperkuat pemikiran kritis dalam pendidikan matematika sekolah dasar.